Cinnamon extract reduces VEGF expression via suppressing HIF‐1α gene expression and inhibits tumor growth in mice. Issue 2 (15th June 2016) - Zhang, Keqiang; Han, Ernest S.; Dellinger, Thanh H.; Lu, Jianming; Nam, Sangkil; Anderson, Richard A.; Yim, John H.; Wen, Wei
Abstract : Although many anti‐VEGF agents are available for cancer treatment, side effects of these agents limit their application for cancer treatment and prevention. Here we studied the potential use of a diet‐based agent as an inhibitor for VEGF production. Using a VEGF reporter assay, our data showed that an extract from cinnamon (CE) was a potent inhibitor of VEGF production in human cancer cells and suggested inhibition might be mediated through the suppression of HIF‐1α gene expression and protein synthesis. Furthermore, CE treatment was found to inhibit expression and phosphorylation of STAT3 and AKT, which are key factors in the regulation of HIF‐1α expression, and significantly reduce angiogenesis potential of cancer cells by migration assay. Consistent with these results, we observed significant suppression of VEGF expression, blood vessel formation, and tumor growth in a human ovarian tumor model in mice treated with CE. Cinnamaldehyde, a major component in cinnamon, was identified as one active component in CE that inhibits VEGF expression. Taken together, our findings provide a novel mechanism underlying anti‐angiogenic and anti‐tumor actions of CE and support the potential use of CE in cancer prevention and treatment. © 2016 Wiley Periodicals, Inc.